2015
DOI: 10.1007/s10461-015-1052-8
|View full text |Cite
|
Sign up to set email alerts
|

Female Condom Use and Adoption Among Men and Women in a General Low-Income Urban U.S. Population

Abstract: HIV prevention is increasingly focused on antiretroviral treatment of infected or uninfected persons. However, barrier methods like male condoms (MC) and female condoms (FC) remain necessary to achieve broad reductions in HIV and other sexually transmitted infections (STI). Evidence grows suggesting that removal of basic obstacles could result in greater FC use and reduced unprotected sex in the general population. We conducted four annual cross-sectional surveys (2009–2012) of urban residents (N = 1614) in lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…This was supported with other antiretroviral treatment as suggested by the results in a study conducted on an urban US population. 15 Data on 2712 subjects were collected through a cross-sectional survey in Tanzania using mass media as a mode of promoting the female condom. In the above study, as well as in a South Africa based study, communication with a peer educator or healthcare provider was found to have a direct positive impact on female condom uptake.…”
Section: Introductionmentioning
confidence: 99%
“…This was supported with other antiretroviral treatment as suggested by the results in a study conducted on an urban US population. 15 Data on 2712 subjects were collected through a cross-sectional survey in Tanzania using mass media as a mode of promoting the female condom. In the above study, as well as in a South Africa based study, communication with a peer educator or healthcare provider was found to have a direct positive impact on female condom uptake.…”
Section: Introductionmentioning
confidence: 99%
“…The same study further reveled that locality, province, age, education level, marital status and employment status of the women sampled were significantly associated with knowledge of the FC while the actual utilisation of the FC was only predicted by province and age group [ 19 ]. On the other hand, positive attitudes, network exposure and peer influences and norms were found to be significantly associated with FC use among a sample of heterosexual males and females in the US, although overall uptake was very low [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…We recommend that behavioral interventions focusing on condom use promotion among women living with HIV could have greater public health impact if they were part of broad positive prevention programs delivered with a gender perspective (including women-initiated prevention options) and developing actions that involve male partners, family planning counseling, community empowerment, mental health and drug abuse treatment, and safe serostatus disclosure settings 11,55 . As seen in the qualitative syntheses, few studies included issues beyond sexual risk behavior and none approached family planning or included women's partners.…”
Section: Discussionmentioning
confidence: 99%
“…The focus on treatment as prevention has achieved recognized success; however, detectable HIV viral loads and imperfect adherence to antiretroviral therapy (ART) were not uncommon. Barrier methods such as condoms remain necessary to achieve broad reduction in HIV and other STI 11,12 , considering that sexual transmission is responsible for most of new HIV cases 9 .…”
Section: Introductionmentioning
confidence: 99%